2013
DOI: 10.1371/journal.pone.0064024
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG Subclasses against Enterovirus Type 71: Neutralization versus Antibody Dependent Enhancement of Infection

Abstract: The emerging human enterovirus 71 (EV71) represents a growing threat to public health, and no vaccine or specific antiviral is currently available. Human intravenous immunoglobulin (IVIG) is clinical used in treating severe EV71 infections. However, the discovery of antibody dependent enhancement (ADE) of EV71 infection illustrates the complex roles of antibody in controlling EV71 infection. In this study, to identify the distinct role of each IgG subclass on neutralization and enhancement of EV71 infection, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…In EV-A71, IgG1 subclass demonstrated the strongest neutralizing ability and is found in human intravenous immunoglobulin [43]. In the present study, IgG1 subclass was identified as the predominant isotype in EV-A71-infected patient sera.…”
Section: Discussionsupporting
confidence: 54%
“…In EV-A71, IgG1 subclass demonstrated the strongest neutralizing ability and is found in human intravenous immunoglobulin [43]. In the present study, IgG1 subclass was identified as the predominant isotype in EV-A71-infected patient sera.…”
Section: Discussionsupporting
confidence: 54%
“…16 Design of such a trial will need to take into account the more recent observation that antibodies may enhance and, hence, worsen EV71 infection severity. 24 Furthermore, Cao et al 25 confirmed that that IVIG manufactured in China had EV71 neutralizing activity, mainly mediated by IgG1 subclass but not by IgG3 subclass. The latter IgG3 subclass fraction enhanced EV71 infection in vitro, 25 again raising concerns regarding IVIG treatment safety.…”
Section: Discussionmentioning
confidence: 96%
“…For example, an early study compared purified subclass antibodies in Herpesvirus neutralization assays, determining that IgG3 and IgG4 had the greatest viral neutralizing ability despite not being the predominant subclass [25]. A further study of responses against human enterovirus 71 found that IgG1 and IgG2 fractions were the most effective at neutralization, and that IgG3 led to enhanced infection [26]. The knowledge obtained from IgG subclass studies, combined with a greater molecular understanding of IgG subclass properties, will facilitate the engineering and development of highly effective CD-specific monoclonal therapeutic antibodies.…”
Section: Discussionmentioning
confidence: 99%